(untitled) (Journal of EAHIL, 2015)
Focus on MLA ’15: “Librarians Without Limits”, Texas, USA, 15-20 May 2015 The US Medical Library Association Annual Meeting will be held in Austin, Texas this year. Austin is theÂ capital city of Texas, though perhaps less well known to many Europeans than some of the other TexanÂ cities such as Dallas or Houston. Even if you...